Determination of Sarafloxacin in Eggs by Flow Injection Chemiluminescence Combined with Solid-Phase Extraction - Liu, Yue-Ying; Zhao*, Shi-Hao (Asian Journal of Chemistry, 2013)
A simple flow injection chemiluminescence method was developed for the rapid and sensitive determination of sarafloxacin in animal eggs. The study based on the chemiluminescence induced by H2O2 and luminol in NaOH medium, sarafloxacin could dramatically enhance chemiluminescence intensities and incorporated with solid-phase extraction. The chemiluminescence system has been applied for the determination of sarafloxacin in eggs. Under optimum conditions, the chemiluminescence intensities were linearly related to the concentration of sarafloxacin in the range of 2.0 × 10-7 to 8.0 × 10-5 g L-1 with a correlation coefficient of 0.9992 and the detection limit was 4.0 × 10-8 g L-1. The relative standard deviation was 2.4 % for 5.0 × 10-6 g L-1 sarafloxacin.